Democratization of Legislative Prospective Candidate Selection: Urgency and Its Parameters - Jamaludin Ghafur (Universitas Ahmad Dahlan, 2021)
Introduction to The Problem: One of the most important functions of political parties in a representative democracy is to recruit or select candidates for public officials. One of which is the selection of legislative candidates. Through this function, political parties will determine whether a person has the quality and capacity to be a member of representative and carry out his role well. Article 241 of Law Number 7 of 2017 concerning General Elections mandates that political parties in selecting candidates must be democratically and openly. But, the criteria of democratic selection is not rigidly regulated because they are fully submitted to be regulated in the internal regulations of political parties.Purpose/Objective Study: This article aims to analyze the urgency of the process of selecting legislative prospective candidate democratically and to find several parameters for the democratic selection of legislative prospective candidate.Design/Methodology/Approach: This is a normative legal research. The research sources consist of primary law and secondary law. It will also use non-legal material sources. Data collection is carried out through literature study.Findings: The results of the research are: First, the urgency of the selection of candidates to be democratically because this mechanism promises some benefits for the societies, political parties, and the quality of democracy in general, i.e: The democratic process of selecting candidates is directly proportional to the satisfaction of the wider community towards the democratic system itself; and tending to produce competent and desired candidates by the public, as well as adopting more responsive policies. Second, the parameters or indicators that can be used as guidelines to determine the democratic selection of candidates will consist of 4 (four) indicators, that are: (1) Candidacy; (2) Selectorates; (3) The level of centralization/ decentralization of selection; and (4) How are candidates nominated?Paper Type: Research Article